PASAK KAYU SEBAGAI BAHAN ALTERNATIF ALAT SAMBUNG PADA KONSTRUKSI KAYU - Gunawan, Firman; Roberth, Herry Henry; Picauly, Fredy (Journal Agregate, 2024)
Pegs are a connecting tool in wood construction that is used as the main material to connect wooden beams with one another wooden beam so that they can be strengthened and united. One of the woods that will be made pegs is merbau wood which is found in Maluku. The research method used is an experimental method carried out through an experiment to obtain information on an object of research. This research was conducted at the Laboratory of the Department of Civil Engineering of Ambon State Polytechnic. The number of specimens used is 9 pieces with a peg diameter of 15 mm and variations in pedestal widths of 20 mm, 30 mm and 40 mm totaling 3 pieces each. Of the three variations of test specimens, there is an average maximum load on each test specimen, namely for a 20 mm pedestal of 15000 N, test specimen 2, a 30 mm pedestal of 16500 N and test specimen 3, a 40 mm pedestal of 17166.67 N and the average shear strength produced is, 42.46 Mpa at a pedestal thickness of 20 mm, 46.71 Mpa for wood thickness of 30 mm,  and 48.59 Mpa for 40 mm wood thickness.